Laponite-Modified Biopolymers as a Conformable Substrate for Optoelectronic Devices - Onishi, Bruno S. D. [UNESP]; Carvalho, Rafael S.; Bortoletto-Santos, Ricardo; Santagneli, Silvia H. [UNESP]; Barreto, Arthur R. J.; Santos, Aline M.; Cremona, Marco; Pandoli, Omar G.; Junior, Mario N. B.; Faraco, Thales A.; Barud, Hernane S.; de Farias, Renan L.; et al. (American Chemical Society (ACS), 2024)
Biopolymers such as carboxymethyl cellulose and hyaluronic acid are alternative substrates for conformable organic light-emitting diodes (OLEDs). However, drawbacks such as mechanical stress susceptibility can hinder the device’s performance under stretched conditions. To overcome these limitations, herein, we developed a nanocomposite based on CMC/HA (carboxymethyl cellulose/hyaluronic acid) and synthetic Laponite, intending to improve the mechanical strength without compromising the film flexibility and transparency (transmittance >80%; 380-700 nm) as substrates for conformable OLEDs. From XRD, FTIR, CP-MAS NMR, and TGA/DTG characterization techniques, it was possible to conclude the presence of Laponite randomly dispersed between the polymer chains. CMC/HA with 5% (w/w) Laponite, CMC/HA 5, presented a higher tensile strength (370.6 MPa) and comparable Young’s modulus (51.0 ± 1.2 MPa) in comparison to the nanocomposites and pristine films, indicating a better candidate for the device’s substrates. To produce the OLED, the multilayer structure ITO/MoO3/NPB/TCTA:Ir(ppy)3/TPBi:Ir(ppy)3/BPhen/LiF was deposited onto the CMC/HA 5 substrate. The OLEDs fabricated using CMC/HA 5 substrates showed higher luminance (12 kcd/m2) and irradiance (0.9 mW/cm2) values when compared with those based on commercial bacterial cellulose. However, the same device presented a lower efficiency (3.2 cd/A) due to a higher current density. Moreover, the OLED fabricated onto the Laponite-modified biopolymer presented reproducible behavior when submitted to continuous bending stress. Thus, CMC/HA 5 demonstrates potential as a transparent conductor substrate for biopolymer-based OLEDs with comparable performance to commercial bacterial cellulose features.